The Role of Mitochondrial Impairment and Oxidative Stress in the Pathogenesis of Lithium-Induced Reproductive Toxicity in Male Mice - Ommati, Mohammad Mehdi; Arabnezhad, Mohammad Reza; Farshad, Omid; Jamshidzadeh, Akram; Niknahad, Hossein; Retana-Marquez, Socorro; Jia, Zhipeng; Nateghahmadi, Mohammad Hassan; Mousavi, Khadijeh; Arazi, Aysooda; Azmoon, Mohammad Reza; Azarpira, Negar; et al. (Frontiers in Veterinary Science, 2021)
Lithium (Li+) is prescribed against a wide range of neurological disorders. Besides its excellent therapeutic properties, there are several adverse effects associated with Li+. The impact of Li+ on renal function and diabetes insipidus is the most common adverse effect of this drug. On the other hand, infertility and decreased libido is another complication associated with Li+. It has been found that sperm indices of functionality, as well as libido, is significantly reduced in Li+-treated men. These adverse effects might lead to drug incompliance and the cessation of drug therapy. Hence, the main aims of the current study were to illustrate the mechanisms of adverse effects of Li+ on the testis tissue, spermatogenesis process, and hormonal changes in two experimental models. In the in vitro experiments, Leydig cells (LCs) were isolated from healthy mice, cultured, and exposed to increasing concentrations of Li+ (0, 10, 50, 100 ppm). In the in vivo section of the current study, mice were treated with Li+ (0, 10, 50, and 100 ppm, in drinking water) for five consecutive weeks. Testis and sperm samples were collected and assessed. A significant sign of cytotoxicity (LDH release and MTT assay), along with disrupted testosterone biosynthesis, impaired mitochondrial indices (ATP level and mitochondrial depolarization), and increased biomarkers of oxidative stress, were detected in LCs exposed to Li+. On the other hand, a significant increase in serum and testis Li+ levels were detected in drug-treated mice. Moreover, ROS formation, LPO, protein carbonylation, and increased oxidized glutathione (GSSG) were detected in both testis tissue and sperm specimens of Li+-treated mice. Several sperm anomalies were also detected in Li+-treated animals. On the other hand, sperm mitochondrial indices (mitochondrial dehydrogenases activity and ATP levels) were significantly decreased in drug-treated groups where mitochondrial depolarization was increased dose-dependently. Altogether, these data mention oxidative stress and mitochondrial impairment as pivotal mechanisms involved in Li+-induced reproductive toxicity. Therefore, based on our previous publications in this area, therapeutic options, including compounds with high antioxidant properties that target these points might find a clinical value in ameliorating Li+-induced adverse effects on the male reproductive system.